An examination of the quality of web disclosure practices through an analysis of firm characteristics, semantic properties and tone / Indah Melati ... [et al.] - Melati, Indah (Accounting Research Institute (ARI), 2022)
This research aimed to measure the quality of voluntary web-disclosure by listed companies in Indonesia, using a voluntary web-disclosure index to capture both quality and quantity of web-disclosures. Focussing on the dimensions of web-content and the presentation of information, this study scored 44 web-disclosure items using a dichotomous score to examine the variety of information and an ordinal score to examine the depth of the disclosure. The findings revealed that on average, the quality of voluntary web-disclosure in Indonesia is relatively low. Disclosure appeared heavily centred on financial information, with information on corporate governance and corporate social responsibility being only moderately disclosed. The differences of firm size and industry type among sample companies were found to be significantly positive when matched to the web-disclosure index. This confirms postulations of the Agency Theory and Signalling Theory which suggest that companies were motivated to signal accountability and transparency through their websites. This study extends prior research on web-disclosure by demonstrating that the use of semantic properties contributes to the richness of examining voluntary web-disclosure as it offers greater insights into the transparent reporting practices by corporate entities.